Smart Linkage to Care : Evaluation Report - Venter, W.D. Francois (World Bank, Washington, DC, 2018)
Many new HIV cases are lost to follow-up before they can be enrolled in care and treatment programs. This report summarises a proof-of-concept evaluation of a mHealth intervention which aims to improve linkage of newly diagnosed HIV cases to care. The design was a randomised controlled multi-center trial enrolling consenting patients in clinics in Inner-city Johannesburg. The trial developed and tested the “SmartLink” app which is designed to make laboratory data directly available to patients via a secure account and send them appointment reminder and notifications on their smartphone. The primary endpoint was linkage to care in the first 8 months after diagnosis, as evidenced by a HIV-related laboratory test. The report provides the key findings on phone ownership of the target group, and which demographics can best be reached via apps and data-based communication (which is cheaper and offers more scope than text messaging). The app worked best in younger HIV patients under 30 years of age, who had their linkage to HIV care improved by 20 percent through the app. This younger age group is difficult to reach with traditional interventions, and reacted positively to a technology solution. The unique feature of this custom-made app (sending real-time CD4/VL test data from the laboratory database to HIV clients) is highly scalable among smartphone owners.